Student Perceptions of Growth-Facilitating and Growth-Constraining Factors of Practice Placements: A Comparison between Japanese and United Kingdom Occupational Therapy Students - Reiko Miyamoto; Dido Green; Peter Bontje; Natsuka Suyama; Nobuo Ohshima; Sally S. A. Fever; Jenny Butler (Occupational Therapy International)
This study compared growth-facilitating and growth-constraining experiences of practice placements as perceived by occupational therapy students from Japan and the United Kingdom (UK). Fifteen students from Japan and 14 from the UK used a nominal group technique (NGT) to rank, individually and in groups, their subjective learning experiences during practice placements. Qualitative analysis and simple tabulation based on ranking of items obtained in the NGT were performed. Five item categories were identified from both Japanese and UK students: self-reflection, the role of supervisor, sense of responsibility, clinical knowledge and skills, and time management. Results showed that all students perceived opportunities for self-reflection and feedback from supervisors as growth facilitating and students’ passive attitudes towards requirements of practice placements as growth constraining. Country-specific differences between students were observed in clinical knowledge and skills, sense of responsibility, and time management. Japanese students perceived that preparatory study led to successfully treating clients during placement, and they tended to commit to placement assignments at the expense of time outside. UK students valued working independently with a sense of responsibility but considered time-management problems within their placement hours as growth constraining. These differences can be explained by different social norms and expectations of students from Japan and the UK.